Jornada dos jovens no percurso da Igreja: análise da Jornada Mundial da Juventude - Batista, Débora Carvalho (2019)
The aim of the present research is to analyze the World Youth Days (WYD), from its beginning to the present day, in order to deepen the study on this event that attracts millions of young people and has been the focus of papal and world attention, in the course of the Catholic Church. The hypothesis is that Pope John Paul II created WYD to reinforce Catholic unity and identity that was weakened, in the context of his pontificate. Francis, at the Journeys, continues the reforms that he aspires to Catholicism, that is, an outgoing Church, which meets the most needy and excluded. It is, therefore, a qualitative bibliographical study on the documents and discourses of the Church and on the theories of Durkheim (1996) and Bauman (2000), in the context of the cohesion and liquidity of events, including those of the Church. Within the obtained results, it is possible to be said of the ephemerality of the Days, considering that the participants do not manage to implement great changes, when the return to their countries of origin. However, it is also said that, in the context of Francis, there is a search for authenticity, cohesion and coherence of attitudes, aiming at mission, humility and concreteness in meeting the poor